Applicability of EU(7)-PIM criteria in cross-national studies in European countries - Fialová, Daniela; Brkić, Jovana; Laffon, Blanca; Reissigová, Jindra; Grešáková, Silvia; Dogan, Soner; Doro, Peter; Tasić, Ljiljana; Marinković, Valentina; Valdiglesias, Vanessa; Costa, Solange; Kostřiba, Jan (Therapeutic advances in drug safety, 2019)
Background: The European Union (EU)(7)-PIM (potentially inappropriate medication) list presents the most comprehensive and up-to-date tool for evaluation of PIM prescribing in Europe; however, several country-specific studies have documented lower specificity of this list on pharmaceutical markets of some countries. The aim of our study was to describe approval rates and marketing of PIMs stated by EU(7)-PIM criteria in six EU countries [in comparison with the American Geriatric Society (AGS) Beers 2015 criteria]. Methods: Research teams of six EU countries (Czech Republic, Spain, Portugal, Serbia, Hungary and Turkey) participated in this study conducted by WG1b EU COST Action IS1402 group in the period October 2015-November 2018. Data on approval rates of PIMs and their availability on pharmaceutical markets have been obtained from databases of national drug-regulatory institutes and up-to-date drug compendia. The EU(7)-PIM list and AGS Beers 2015 Criteria (Section 1) were applied. Results: PIMs from EU(7)-PIM list were approved for clinical use more often than those from the AGS Beers 2015 criteria (Section 1). Approval rates for EU(7)-PIMs ranged from 42.8% in Serbia to 71.4% in Spain (for AGS criteria only from 36.4% to 65.1%, respectively). Higher percentages of approved PIMs were documented in Spain (71.4%), Portugal (67.1%) and Turkey (67.5%), lower in Hungary (55.5%), Czech Republic (50.2%) and Serbia (42.8%). The majority of approved PIMs were also currently marketed in all countries except in Turkey (19.8-21.7% not marketed PIMs) and less than 20% of PIMs were available as over-the-counter medications (except in Turkey, 46.4-48.1%). Conclusions: The EU(7)-PIM list was created for utilization in European studies; however, applicability of this list is still limited in some countries, particularly in Eastern and Central Europe. The EU project EUROAGEISM H2020 (2017-2021) that focuses on PIM prescribing and regulatory measures in Central and Eastern European countries must consider these limits.